Distribution and seasonal variation of Ljungan virus in bank voles (Myodes glareolus) in Fennoscandia - Fevola, Cristina; Rossi, Chiara; Rosa, Roberto; Nordström, Åke; Ecke, Frauke; Magnusson, Magnus; Miller, Andrea; Niemimaa, Jukka; Olsson, Gert; Jääskeläinen, Anne; Hornfeldt, Birger; Henttonen, Heikki; et al. (Wildlife Disease Association, 2017)
Ljungan virus (LV) is a picornavirus originally isolated from Swedish bank voles (Myodes glareolus) in 1998. The association of LV with human disease has been debated ever since, but fundamental data on the ecology of the virus are still lacking. Here we present results of the first intensive study on the prevalence of LV in bank voles trapped in Fennoscandia (Sweden and Finland) from 2009-12 as determined by PCR. Using an LV-specific real-time reverse transcriptase PCR, LV was detected in the liver of 73 out of 452 (16.2%) individuals and in 13 out of 17 sampling sites across Sweden and Finland (mean per site prevalence 16%, SE 3%, range 0-50%). We found more infected animals in autumn compared to spring, and lighter and heavier individuals had a higher prevalence than those with intermediate body masses. The result that LV prevalence is also lower in heavier (i.e., older) animals suggests for the first time that LV infection is not persistent in rodents.
Keywords: Parechovirus B; picornavirus; rodent-borne virus; Suomi; Ruotsi; jyrsijät; myyrät; rodents; voles